DESAIN APLIKASI MODUL PEMBELAJARAN BAHASA INDONESIA BERBASIS ANDROID - Sabila Amalia Fitri; Teguh Khristianto; Isworo Nugroho (STEKOM PRESS, 2022)
The module is a book written with the aim that students can learn independently and in the module contains the basic components of teaching materials so that students can understand easily. The advantages and disadvantages of the module are that students can learn independently using the module and the teacher is no longer the only source of learning for students. Education has used various ways in theteaching and learning process. One of the general users of website users in public schools is the use of web-based learning aplications that contain tutorials, exercises or vidios that are developed and uploaded to web.